(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Phantoms can be used as quality control objects in computed tomography (CT) imaging and dosimetry in specific regions of interest. By means of phantom tests, alternatives can be created to optimize the acquisition protocols and thus modify the acquisition parameters to deposit lower levels of radiation to the patient, seeking a quality image for the diagnosis. Radiochromic films, GAFCHROMIC XR-AQ2 model, are used to measure the dose-response when exposed to radiation. The profile of the absorbed dose within a phantom is important because it allows an understanding of a larger reality. Calibration curves were obtained from radiochromic films using a cylindrical phantom made of polymethyl methacrylate (PMMA). This phantom has five openings, one central and four peripherals lagged 90°. The phantom was positioned in the isocenter of the gantry of a scanner manufactured by the Toshiba, model Asterion, using 120 and 135 kV voltage of the X-ray tube. The phantom peripheral openings were positioned similarly to positions 3, 6, 9, and 12 of the analog clock. The ionization chamber was used for the record values of the Air Kerma in PMMA, in the central and 12 positions when the central slice of the phantom was irradiated in the axial mode. The other openings were filled with rods also made of PMMA. Radiochromic film strips were placed into PMMA rods and the central and 12 openings were filled. The central area of the phantom was scanned in helical mode. The film strips were digitized and processed their images to have the calibration curve survey.